PENGELOLAAN TANAH ADAT PADA MASYARAKAT ADAT BATAK TOBA DI KELURAHAN BARISAN PANCUR NAULI KOTA PEMATANG SIANTAR - Hendra Pranata; Hayatul Ismi; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Legal actions involving customary land that often occur are the pawn of customary land, Bataktoba indigenous people are more familiar with the term pawn. In this pate, traditional customary land canbe transferred to the owner even though the new owner is not from the inheritance line or a member of atraditional association (huta). The problem that often also occurs is when a family has ownership rightsover a customary land but the family does not have a lineage to inherit the customary land. If this happensto which party will receive from the ownership rights of the customary land. Of course this would be adebate among various parties in the village if the previous customary landowners did not give a will on therights of the customary land. Based on the background described above, the authors were interested inconducting research relating to the management of customary land to indigenous peoples. The title of theauthor was: "Management of Customary Land in the Toba Batak Indigenous Peoples in the Village ofBarisan Pancur Nauli, Pematang Siantar City."Based on the description of the background of the problem, the authors formulated the problem asfollows: first, namely, what is the background of customary land management of the Toba Batak indigenouspeople in the Village of Barisan Pancur Nauli, Pematang Siantar City? Second, what efforts should be madeby indigenous peoples in managing customary lands that are in accordance with customary landmanagement in the Toba Batak indigenous people in the Barisan Pancur Nauli Sub-District, PematangSiantar City?The conclusion of the study by the author that the Background of Customary Land Management inthe Toba Batak Indigenous Peoples in Barisan Pancur Nauli Subdistrict, Pematang Siantar City, was foundto be dominated by four clans namely Tampubolon, Simangungsong, Napitupulu, and Sianipar, landmanagement by selling land, pawning land and leasing land soil. Efforts made by the Toba Batakindigenous people still adhere to the Dalihan no tofu principle, which is one of peaceful dispute resolutionwithout involving things that harm many people. Suggestions from the authors are that efforts to buy andsell customary land so the government can participate in avoiding unwanted conflicts , then preventing thesale and purchase of land to outsiders so that the customary land is maintained and always exists.Keywords: Toba Batak Land Management